2018
DOI: 10.1111/iej.12904
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of silver nanoparticles as a root canal irrigant against Enterococcus faecalis biofilm and infected dentinal tubules

Abstract: AgNp irrigant was not as effective against E. faecalis compared to solutions commonly used in root canal treatment. NaOCl is appropriate as an irrigant because it was effective in disrupting biofilm and in eliminating bacteria in biofilms and in dentinal tubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 41 publications
8
70
2
6
Order By: Relevance
“…In contrast, the microbiological evaluation confirmed the highly effective antibacterial activity of NaOCl on a biofilm of Enterococcus faecalis ( Figure 6). Our results agree with those of previous studies showing that a 5.25% NaOCl solution was able to remove organic and loose superficial debris but was not totally effective in removing inorganic smear layer [30,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the microbiological evaluation confirmed the highly effective antibacterial activity of NaOCl on a biofilm of Enterococcus faecalis ( Figure 6). Our results agree with those of previous studies showing that a 5.25% NaOCl solution was able to remove organic and loose superficial debris but was not totally effective in removing inorganic smear layer [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…A possible elucidation to the mechanism of action of silver on an E. faecalis biofilm is that silver ions and nanoparticles may be able to interact and penetrate the cell membrane of both Gram-positive and Gram-negative bacteria, causing damage to deoxyribonucleic acid and finally death of bacteria by liberating silver ions. Moreover, silver may have an intrinsic peroxidase-like activity, which can catalyze hydrogen peroxides (PBS 2 ) to generate free radicals in a pH-dependent manner [31,39]. Yamaguchi et al [40] reported that low concentration (0.5, 1, 2 M) citric acid solutions could have an antimicrobial potential against anaerobic bacteria species when employed as potential irrigation solutions for root canals.…”
Section: Discussionmentioning
confidence: 99%
“…, Rodrigues et al . ). For biofilm analysis 4 images per dentine block were obtained, totalling 20 per each biofilm group.…”
Section: Methodsmentioning
confidence: 97%
“…The samples size was based on previous studies that used similar antimicrobial analysis (Zancan et al 2016, Rodrigues et al 2018. For biofilm analysis 4 images per dentine block were obtained, totalling 20 per each biofilm group.…”
Section: Confocal Laser Scanning Microscopy (Clsm) Analysismentioning
confidence: 99%
“…Sodium hypochlorite (NaOCl) and chlorhexidine (CHX) have been widely used as root canal irrigants because of their antimicrobial ability against endodontic bacteria (Goncalves et al 2016). NaOCl remains the most recommended root canal irrigant due to its strong antimicrobial efficacy and its ability to dissolve organic matter (Guerreiro‐Tanomaru et al 2014, Rodrigues et al 2018). However, NaOCl can be harmful and cytotoxic to the host tissue and has a distinctive smell and taste (Segu et al 2018, Slaughter et al 2019).…”
Section: Introductionmentioning
confidence: 99%